2015
DOI: 10.1093/mnras/stv1226
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and MOND dynamical models of the massive spiral galaxy NGC 2841

Abstract: We study dynamical models of the massive spiral galaxy NGC 2841 using both the Newtonian models with Navarro-Frenk-White (NFW) and isothermal dark haloes, as well as various MOND (MOdified Newtonian Dynamics) models. We use the observations coming from several publicly available data bases: we use radio data, near-infrared photometry as well as spectroscopic observations. In our models, we find that both tested Newtonian dark matter approaches can successfully fit the observed rotational curve of NGC 2841. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We indeed found many signs of recent interactions in the galaxies that were most problematic for MOND. Finally, we briefly discuss the recent findings of Samurović and Vudragović (2019) related to two massive nearby ETGs, NGC 4473 and NGC 4697 26 , both fast rotators. Newtonian (purely baryonic and also models based on the Einasto (1965) DM profile) and MOND models were tested using GCs as tracers of gravitational potential of the galaxies.…”
Section: Globular Clusters (Gcs)mentioning
confidence: 97%
See 2 more Smart Citations
“…We indeed found many signs of recent interactions in the galaxies that were most problematic for MOND. Finally, we briefly discuss the recent findings of Samurović and Vudragović (2019) related to two massive nearby ETGs, NGC 4473 and NGC 4697 26 , both fast rotators. Newtonian (purely baryonic and also models based on the Einasto (1965) DM profile) and MOND models were tested using GCs as tracers of gravitational potential of the galaxies.…”
Section: Globular Clusters (Gcs)mentioning
confidence: 97%
“…It is important to stress that the contribution of the stellar component was not based on the central parts only but was a function of radius (see Fig. 5 in Samurović and Vudragović 2019): the value of the stellar mass-to-light ratio in the B-band varies between approximately 7 in the inner regions to 3 in the outer regions. Three cases of anisotropies were tested and it was found that in most tested cases Newtonian purely baryonic models for both galaxies could not provide a successful fit of the observed velocity dispersion without the additional dark component and that the introduction of the dark Einasto halo improved the quality of the fits.…”
Section: Globular Clusters (Gcs)mentioning
confidence: 99%
See 1 more Smart Citation